Forecasting and assessing Euro area house prices through the lens of key fundamentals - Luca Gattini; Paul Hiebert (European Central Bank (ECB), 2010)
This paper presents a parsimonious model for forecasting and analysing euro area house prices and their interrelations with the macroeconomy. A quarterly vector error correction model is estimated over 1970-2009 using supply and demand forces central to the determination of euro area house prices in equilibrium and their dynamics: housing investment, real disposable income per capita and a mixed maturity measure of the real interest rate. In addition to house price forecasts using the resulting reduced form equation, a structural decomposition of the system is obtained employing a common trends framework of King, Plosser, Stock, and Watson (1991), which allows for the identification and economic interpretation of permanent and transitory shocks. The main results are twofold. First, the reduced form model tracks closely turning points in house prices when examining out-of-sample one- and two- step ahead forecasts. Moreover, the model suggests that euro area housing was overvalued in recent years, implying a period of stagnation to bring housing valuation back in line with its modelled fundamentals. Second, housing demand and financing cost shocks appear to have contributed strongly to the dynamism in euro area house prices over the sample period. While much of the increase appears to reflect a permanent component, a transitory component has also contributed from 2005 onwards. Specification tests suggest a robustness of the small model to alternative specifications, along with validity of the long-run restrictions.
Keywords: R21; R31; C32; 330; forecasting; house price; Vector autoregression; Immobilienpreis; Prognoseverfahren; VAR-Modell; Modellierung; EU-Staaten